Application of Solid-State NMR to Reveal Structural Differences in Cefazolin Sodium Pentahydrate From Different Manufacturing Processes - Tian, Ye; Wang, Wei D.; Zou, Wen-Bo; Qian, Jian-Qin; Hu, Chang-Qin (Frontiers in Chemistry, 2018)
The solid form of an active pharmaceutical ingredient is important when developing a new chemical entity. A solid understanding of the crystal structure and morphology that affect the mechanical and physical characteristics of pharmaceutical powders determines the manufacturing process. Solid-state NMR, thermogravimetric analysis, X-ray diffraction, and Fourier-transform infrared spectroscopy were combined with theoretical calculation to investigate different crystal packings of α-cefazolin sodium from three different vendors and conformational polymorphism was identified to exist in the α-cefazolin sodium. Marginal differences observed among CEZ-Na pentahydrate 1, 2, and 3 were speculated as the proportion of conformation 2. Understanding the differences in the polymorphic structure of α-cefazolin sodium may help with making modifications to incorporate new knowledge with a product’s development.